Franklin D. Roosevelt [compact disc, unabridged] : a political life - Dallek, Robert (Penguin Audio, 2017)
A portrait of the thirty-second president focuses on his career as a politician and dealmaker whose unusual skills served to unite divided factions, initiate essential reforms, and transform America into an international superpower.